2014
DOI: 10.1186/1476-069x-13-98
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide use, erythrocyte acetylcholinesterase level and self-reported acute intoxication symptoms among vegetable farmers in Nepal: a cross-sectional study

Abstract: BackgroundAs pesticide use is increasing and proper handling training is lacking, exposure to pesticides and intoxications are an important public health problems among farmers in developing countries. This study describes pesticide use among farmers and compares symptoms of possible acute intoxication and Erythrocyte Acetylcholinesterase(AChE) levels among vegetable farmers with a control group of blood donors in Nepal.MethodsA cross-sectional study was carried out among 90 pesticide-exposed farmers and a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
48
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 28 publications
8
48
0
10
Order By: Relevance
“…However, a study done in Nepal by Neupane et al 15 reported a higher number of possible symptoms (4.78) of acute intoxication. Another study done in Indonesia by Kishi et al 16 reported that farmers had four signs/symptoms on an average, which is a very high level of intoxication and thereby creates an urgent need of increasing awareness among the commercial farmers.…”
Section: Discussionmentioning
confidence: 97%
“…However, a study done in Nepal by Neupane et al 15 reported a higher number of possible symptoms (4.78) of acute intoxication. Another study done in Indonesia by Kishi et al 16 reported that farmers had four signs/symptoms on an average, which is a very high level of intoxication and thereby creates an urgent need of increasing awareness among the commercial farmers.…”
Section: Discussionmentioning
confidence: 97%
“…The studies of human exposures to pesticides in Nepal have typically focused on occupational exposures [16,[62][63][64], or cases of pesticide poisoning and acute symptoms of pesticide exposure [65][66][67][68][69]. Studies of residential use of pesticides in Nepal have generally assessed methods for managing sand fly populations to control visceral leishmaniasis [70][71][72][73][74].…”
Section: Discussionmentioning
confidence: 99%
“…None of those who protect themselves wear all the personal protection equipment (PPE) normally recommended. Contrarily, Neupane et al (2014) reports that only 13% of farmers did not use any PPE while spraying pesticides in the field. Most farmers use only gloves (13.73%), temporary mufflers (5.66%), hats (0.44%) and boots (0.44%) in addition to their usual farm clothes.…”
Section: Poisoning Risks Behaviorsmentioning
confidence: 99%
“…The gloves are therefore the most widely used personal protection equipment. Neupane et al (2014) found that about 46% of farmers used dust mask to protect against pesticide while spraying in the field and 33% farmers used long legged trousers or pants in Nepal. The percentage of respondents who used glass, gowns, boots and gloves was less than 10% (Neupane and Jørs, 2014).…”
Section: Poisoning Risks Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation